2015
DOI: 10.4103/2008-7802.156838
|View full text |Cite
|
Sign up to set email alerts
|

Awareness about "Ten steps for successful breastfeeding" among medical and nursing students

Abstract: Background:Baby-friendly Hospital Initiative (BFHI) is a vital intervention supported by World Health Organization and UNICEF to reduce infant mortality and has been included as a part of the curriculum in nursing and medical courses. To know the extent of knowledge of students about BFHI along with its understanding and to find out the gap in their knowledge about BFHI steps.Methods:A descriptive cross sectional study was carried out among the nursing (4th year) and medical students (3rd year MBBS) about ten … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 10 publications
1
24
0
Order By: Relevance
“…Three studies reported the validity and reliability of the instruments used [ 16 – 18 ]. Some of these studies collected data before and/or after standard theory and laboratory based learning in maternal and child health curriculum and or clinical placement [ 6 , 13 , 16 , 17 , 19 , 20 ]. However these studies were not designed to evaluate the standard curriculum.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three studies reported the validity and reliability of the instruments used [ 16 – 18 ]. Some of these studies collected data before and/or after standard theory and laboratory based learning in maternal and child health curriculum and or clinical placement [ 6 , 13 , 16 , 17 , 19 , 20 ]. However these studies were not designed to evaluate the standard curriculum.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies described the current undergraduate curriculum indicating that breastfeeding was addressed during the maternal and child health subject. If described, these standard curriculum primarily consisted of classroom and clinical components, discussing topics such as the properties of breast milk, benefits of breastfeeding for both mother and infant, assessment parameters for effective breastfeeding, maternal support, and achievement of proper latch in a didactic instructional manner [ 6 , 16 , 19 , 20 ]. In addition, practical experience was offered through clinical placement at a hospital based maternity unit where nursing students had opportunities to observe and interact with lactation consultants and nurses as they provided breastfeeding support for new mothers [ 6 , 13 , 16 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore the education of BF medicine needs to be executed in medical school and nursing school. Kakrani et al [ 16 ] have studied the awareness about the Ten Steps for successful BF policy among medical students and nursing students in India. They were well aware about step 2 (training), step 6 (no supplement), step 7 (rooming-in), and step 9 (no pacifier).…”
Section: The Importance Of Breastfeeding Education For Medical Studenmentioning
confidence: 99%
“…12 With all these benefits still breastfeeding perception and practices are limited .Health care professionals can play a vital role in promoting breastfeeding. 13,14 It is therefore necessary that medical students acquire knowledge regarding breastfeeding during their period of study. 15 Although they have positive attitude towards breastfeeding, but their knowledge is lacking and perception varied.…”
Section: Introductionmentioning
confidence: 99%